Analysis of Logistic Administration Processes in Supporting the Export of Processed Seafood Products at CV Pasific Harvest - Evi Suwarni; Baroroh Lestari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the logistic administration processes at CV Pasific Harvest and their significance in supporting the export of processed seafood products. Efficient logistics, including inventory management, stock opname, and export documentation, are critical for maintaining product quality and meeting international market demands. The study aims to evaluate strengths, weaknesses, and opportunities in the company's logistic processes to enhance export efficiency. A qualitative case study design was employed, utilizing data collected through interviews with logistic staff, observations of warehouse practices, and analysis of logistic records and export documentation. The results highlight the effective implementation of the First In, First Out (FIFO) system, regular stock opname, and detailed documentation practices, which significantly improve operational accuracy and reduce waste. However, challenges such as damaged goods due to improper stacking during storage and dependency on a limited supplier base were identified as areas for improvement. Proposed solutions include stricter storage and handling guidelines, supplier diversification, and the adoption of digital tools for inventory and documentation management to enhance efficiency and accuracy.This study concludes that CV Pasific Harvest’s optimized logistic administration contributes to its competitive advantage by ensuring product consistency and reliability in international markets. Addressing existing challenges and leveraging identified strengths can further enhance its operational efficiency and market position. These findings provide valuable insights for similar industries aiming to improve their export logistics and adapt to global market dynamics.